2007
DOI: 10.1258/096914107782912095
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with referral compliance of abnormal immunochemical faecal occult blood test

Abstract: Objective This study investigated factors associated with the referral compliance of positive immunochemical faecal occult blood test (iFOBT). Setting Data were from a subset of people who received iFOBT at Taipei county of Taiwan in 2005. Methods All subjects with positive iFOBT were referred to hospital for further diagnostic examinations. In total, 226 such subjects who did not accept referral within 60 days were identified as the non-compliant group from the record of Public Health Bureau. Frequency-matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Cues for action, including “physician's recommendation”; “family history of colorectal cancer”; “experience of bowel habit change or other's experience of undergoing colonoscopy”; and “ past history of tarry stool, bloody stool, or any bowel habit change,” had a great impact on individual's willingness to undergo colonoscopy. These findings were consistent with previous studies . In Taiwan, many physicians are not familiar with the benefits of FIT screening, are unaware of its improved performance compared with the chemical FOBT, and have a doubtful attitude about the result.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Cues for action, including “physician's recommendation”; “family history of colorectal cancer”; “experience of bowel habit change or other's experience of undergoing colonoscopy”; and “ past history of tarry stool, bloody stool, or any bowel habit change,” had a great impact on individual's willingness to undergo colonoscopy. These findings were consistent with previous studies . In Taiwan, many physicians are not familiar with the benefits of FIT screening, are unaware of its improved performance compared with the chemical FOBT, and have a doubtful attitude about the result.…”
Section: Discussionsupporting
confidence: 90%
“…These findings were consistent with previous studies. [22][23][24][25] In Taiwan, many physicians are not familiar with the benefits of FIT screening, are unaware of its improved performance compared with the chemical FOBT, and have a doubtful attitude about the result. Because of this lack of knowledge, many FIT-positive patients are told that it is "not necessary to undergo colonoscopy" or that the FIT test was repeated by their physician, as reported by 4% of our study population.…”
Section: Discussionmentioning
confidence: 99%
“…Socio-demographic characteristics such as maternal education, ethnicity and parity; economic status as well as infant medical history such as prematurity and hospital admission in the neonatal period have been associated with follow-up default in infant hearing screening programmes [ 11 , 13 , 14 ], similar to findings in other screening programmes [ 15 , 16 ]. For instance, one study found that socio-demographic factors such as young maternal age, having more than two children at home (parity), being non-white (race), substance abuse, late onset of prenatal care and lack of health insurance were predictive of non-compliance with hearing screening protocol [ 13 ].…”
Section: Introductionmentioning
confidence: 66%
“…Future studies addressing these issues as well as the impact of culture and beliefs should therefore be considered. For example, a study using an adapted version of the Health Belief Model would be valuable to establish the possible role of individual and community beliefs on deafness across the domains of perceived susceptibility, severity, benefits and barriers [ 15 , 29 ].…”
Section: Discussionmentioning
confidence: 99%